2018
DOI: 10.29333/ejgm/93460
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and associated factors among kidney transplant recipients

Abstract: Background: Depression is one of the most prevalent psychological disorders experienced by kidney transplant (KT) recipients. The aim of this study was to determine the depressive symptoms exhibited by KT recipients and the related factors affecting them. Methods: This descriptive-analytical cross-sectional study was conducted on 131 KT recipients referring to nephrology clinic of Imam Khomeini Hospital, Ardabil, in 2016. Convenience sampling method was employed. Data were collected using personal profile form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A recent study has suggested promotion of self-efficacy and self-care behaviors for depressive symptoms of KTRs [42]. One of the self-care behaviors could be in maintaining healthy dietary habits and lifestyle changes in order to reduce body weight and change the body composition by enhancing muscle mass and reducing fat mass.…”
Section: Laboratory Parameters and Depression In Dalmatian Ktrsmentioning
confidence: 99%
“…A recent study has suggested promotion of self-efficacy and self-care behaviors for depressive symptoms of KTRs [42]. One of the self-care behaviors could be in maintaining healthy dietary habits and lifestyle changes in order to reduce body weight and change the body composition by enhancing muscle mass and reducing fat mass.…”
Section: Laboratory Parameters and Depression In Dalmatian Ktrsmentioning
confidence: 99%